Cysteine-specific fluorescent switch for monitoring oxidative stress and quantification of aminoacylase-1 in blood serum - Anila, H. A.; Ali, Firoj; Kushwaha, Shilpi; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Analytical Chemistry, 2016)

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.

Chitosan-thiobarbituric acid: a superadsorbent for mercury - Bhatt, Rahul; Kushwaha, Shilpi; Bojja, Sreedhar; Padmaja, P. (ACS Omega, 2018)
In the present investigation, chitosan (CH) as supramolecularly cross-linked with thiobarbituric acid to form CT. CT was well characterized by UV, scanning electron microscopy-energy-dispersive X-ray analysis, Fourier trans form infrared, NMR, differential scanning calorimetry, thermogravimetric analysis, and X-ray difTraction analyses, and its adsorption potential for elemental mercury (Hg-0), inorganic mercury (Hg2+), and methyl mercury (CH3Hg+) was investigated. Adsorption experiments were conducted to optimize the parameters for removal of the mercury species under study, and the data were analyzed using Langmuir, Freundlich, an Temkin adsorption isotherm models. CT was found to have high adsorption capacities of 1357.69, 2504.86, and 2475.38 rng/g for Hg-0, Hg2+, and CH3Hg+, respectively. The adsorbent CT could be reused up elemental mercury using 0.01 N thiourea, inorganic mercury using 0.01 N perchloric acid, and methyl to three cycles by eluting mercury with 0.2 N NaCl.